2019
DOI: 10.1038/s41398-019-0584-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene network analysis reveals a role for striatal glutamatergic receptors in dysregulated risk-assessment behavior of autism mouse models

Abstract: Autism spectrum disorder (ASD) presents a wide, and often varied, behavioral phenotype. Improper assessment of risks has been reported among individuals diagnosed with ASD. Improper assessment of risks may lead to increased accidents and self-injury, also reported among individuals diagnosed with ASD. However, there is little knowledge of the molecular underpinnings of the impaired risk-assessment phenotype. In this study, we have identified impaired risk-assessment activity in multiple male ASD mouse models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…This in silico approach to the investigation of unknown biology stems from the "guilt by association" paradigm [33], which is predicated on the assumption that protein products of highly co-expressed (i.e., coordinately transcribed) genes share functionality, forming multi-gene subsystems within a parent biological system [34][35][36]. Weighted gene co-expression network analysis (WGCNA) [27,37] is a technique that has been successfully deployed in this context to study how genes jointly affect complex human diseases [38][39][40][41][42]. We sought to apply this paradigm to 3q29Del syndrome to glean biological insights into disease-associated driver genes and functional mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This in silico approach to the investigation of unknown biology stems from the "guilt by association" paradigm [33], which is predicated on the assumption that protein products of highly co-expressed (i.e., coordinately transcribed) genes share functionality, forming multi-gene subsystems within a parent biological system [34][35][36]. Weighted gene co-expression network analysis (WGCNA) [27,37] is a technique that has been successfully deployed in this context to study how genes jointly affect complex human diseases [38][39][40][41][42]. We sought to apply this paradigm to 3q29Del syndrome to glean biological insights into disease-associated driver genes and functional mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Five DEGs showed consistent expression patterns in all five datasets: three upregulated DEGs (Adi1, Scg5, and Serpina3n), and two downregulated DEGs (Nudt19 and Pop4). The expression patterns of 136 DEGs (23 upregulated, 113 downregulated) were consistent between the BTBR/R mice cerebral cortex and striatum and the BTBR/J mice striatum (Oron et al, 2019) datasets, while those of 30 DEGs (6 upregulated, 24 downregulated) were consistent between the BTBR/R mice cerebral cortex and striatum and the BTBR/J mice cerebral cortex (Daimon et al, 2015) datasets (Supplementary Table 14). In total, 208 DEGs showed consistent expression patterns (45 upregulated, 163 downregulated) between the BTBR/R cerebral cortex and striatum and BTBR/J hippocampus (Provenzano et al, 2016) datasets.…”
Section: Fifty-three Asd Candidate Genes Were Included In Degs Betweementioning
confidence: 84%
“…These results suggested that BTBR/R mouse brains have alterations in Kdm5b-mediated epigenetic regulation commonly affected in these ASD models together with those in the maternal immune activation model. We next examined DEGs between two sublines of BTBR mice by comparing our BTBR/R vs. B6 dataset (1,280 DEGs obtained from the cerebral cortex and striatum) with the five independent BTBR/J vs. B6 datasets (1,016 DEGs from the hippocampus by Provenzano et al (2016); 325 DEGs from the cerebellum by Shpyleva et al (2014); 448 DEGs in the striatum by Oron et al (2019); and 328 DEGs from the hippocampus and 328 DEGs from the cerebral cortex by Daimon et al, 2015; Supplementary Table 14). The 341 DEGs identified in our BTBR/R study were also reported as DEGs in at least one of the BTBR/J datasets.…”
Section: Fifty-three Asd Candidate Genes Were Included In Degs Betweementioning
confidence: 99%
“…In our analysis, we highlighted transcriptomic alterations in glutamatergic and GABAergic signaling pathway genes ( Figure 7B), and the corresponding genes were found to be altered not only in BTBR/R but also BTBR/J mice in several instances (Supplementary Table 14). Among the glutamatergic signaling pathway genes, the glutaminase (Gls), phospholipase A2 group IVB (Pla2g4b), and phospholipase A2 group IVE (Pla2g4e) genes were also altered in the hippocampus (Provenzano et al, 2016), dorsal striatum (Oron et al, 2019), and cerebellum (Shpyleva et al, 2014). Of the GABAergic signaling pathway genes, the GABA receptor subunit gamma-2 (Gabrg2) and GABA-A receptor subunit alpha2 (Gabra2) genes were also altered in the hippocampus (Provenzano et al, 2016), cortex (Daimon et al, 2015), and cerebellum (Shpyleva et al, 2014).…”
Section: Transcriptomic Features Of Neurotransmitter Systemsmentioning
confidence: 99%
“…From this point of view, BTBR/J is a valuable animal model of ASD to analyze the molecular and pathological mechanism at the gene and protein expression level. For this purpose, BTBR/J mice have been subjected to transcriptome analyses of the hippocampus (Daimon et al, 2015;Provenzano et al, 2016;Gasparini et al, 2020), frontal cortex (Kratsman et al, 2016), dorsal striatum (Oron et al, 2019), and cerebellum (Shpyleva et al, 2014), as well as proteome analyses of cortical (Jasien et al, 2014;Wei et al, 2016) and hippocampal tissues (Jasien et al, 2014;Daimon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%